2002
DOI: 10.1074/jbc.m111349200
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat Interaction with RNA Polymerase II C-terminal Domain (CTD) and a Dynamic Association with CDK2 Induce CTD Phosphorylation and Transcription from HIV-1 Promoter

Abstract: Human immunodeficiency virus, type 1 (HIV-1), Tat protein activates viral gene expression through promoting transcriptional elongation by RNA polymerase II (RNAPII). In this process Tat enhances phosphorylation of the C-terminal domain (CTD) of RNAPII by activating cell cycle-dependent kinases (CDKs) associated with general transcription factors of the promoter complex, specifically CDK7 and CDK9. We reported a Tat-associated T-cell-derived kinase, which contained CDK2. Here, we provide further evidence that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
107
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 35 publications
0
107
0
Order By: Relevance
“…Such broad protein kinase substrate specificity is not too surprising, because Ͼ20 isoforms of CDK11 p110 are produced ubiquitously in all human cells (18). In addition, others have shown that TAT-SF1 U-snRNP complexes containing CDK9 and cyclin T proteins stimulate splicing in vitro, possibly facilitating the reciprocal activation of transcription and splicing events through its ability to function as a dual-function factor (19).…”
mentioning
confidence: 99%
“…Such broad protein kinase substrate specificity is not too surprising, because Ͼ20 isoforms of CDK11 p110 are produced ubiquitously in all human cells (18). In addition, others have shown that TAT-SF1 U-snRNP complexes containing CDK9 and cyclin T proteins stimulate splicing in vitro, possibly facilitating the reciprocal activation of transcription and splicing events through its ability to function as a dual-function factor (19).…”
mentioning
confidence: 99%
“…Reports have been published that CDK group, especially the CDK2, is involved in the transcription and replication of Human Immunodeficiency Virus -1 by means of phosphorylation [22], [23]. Previous studies [8], [24] also show that CK2 group phosphorylates Hepatitis C Virus NS5A proteins and Human Immunodeficiency Virus -1 gp120, gp41, p27, and p17 proteins to name a few, on both S and T residues.…”
Section: Motifs Comparisonmentioning
confidence: 99%
“…Cyclindependent kinase 2 (CDK2) is a catalytic subunit of the cyclindependent protein kinase complex, whose activity is restricted to the G1-S phase, and which is essential for transition of the cell cycle from G1 to S phase. CDK2 phosphorylates HIV Tat protein, a step that is important for HIV-1 transcription [41,42].…”
Section: Ppi Clusters Spanned By Bkz Hdfs and Ss+ Predicted Hdfs Are mentioning
confidence: 99%